Overhaul : A Social History of the Albuquerque Locomotive Repair Shops - Flint, Richard, 1946-; Flint, Shirley Cushing (Book collections on Project MUSE., 2021)
In Overhaul, historians Richard Flint and Shirley Cushing Flint present the largely forgotten story of Albuquerque's locomotive repair shops, which were the driving force behind the city's economy for more than seventy years.